SUNFLOWER METAPHOR IN DA'WAH THROUGH MUSIC : Analysis of Spirituality and the Meaning of the Song 'Gala Bunga Matahari' by Sal Priadi - Putri Isma Indriyani; Makrifatul Illah (Fakultas Dakwah dan Komunikasi UIN Sunan Kalijaga, 2024)
This study explores da'wah's spiritual and communicative aspects embedded in Sal Priadi's song